Beet Armyworm, Spodoptera exigua (Hübner) (Insecta: Lepidoptera: Noctuidae): EENY-105/IN262, 7/1999 - Capinera, John L. (EDIS, 2002)
This document is EENY-105, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 1999. EENY105/IN262: Beet Armyworm, Spodoptera exigua (Hübner) (Insecta: Lepidoptera: Noctuidae) (ufl.edu)